Intimate Partner Violence and Self-Reported Pre-exposure Prophylaxis Interruptions Among HIV-Negative Partners in HIV Serodiscordant Couples in Kenya and Uganda. (1st February 2018) - Cabral, Alejandra; M. Baeten, Jared; Ngure, Kenneth; Velloza, Jennifer; Odoyo, Josephine; E. Haberer, Jessica; Celum, Connie; Muwonge, Timothy; Asiimwe, Stephen; Heffron, Renee
Abstract : Background: Oral pre-exposure prophylaxis (PrEP) is effective for HIV prevention, and PrEP delivery studies are investigating ways to deliver PrEP with high adherence. However, in many settings with high HIV burden, intimate partner violence (IPV) is reported often and could be a barrier to the effective PrEP use. We examined the association between IPV and interruptions in PrEP use. Methods: We analyzed data from 1013 serodiscordant heterosexual couples enrolled in a large PrEP demonstration project in Kenya and Uganda, the Partners Demonstration Project. At quarterly study visits, HIV-negative participants receiving PrEP were asked about interruptions in their PrEP use and experiences with IPV. The association between IPV and PrEP interruptions was analyzed using multivariable generalized estimating equations. Results: At baseline and follow-up, there were 53 visits with reports of abuse by 49 HIV-negative partners, including physical, economic, and verbal IPV. Interruptions in PrEP use were reported at 328 visits (7.1% of all visits) by 249 people. The median length of PrEP interruption was 28 days (interquartile range: 7–45). The frequency of PrEP interruptions among those reporting IPV was 23.8% and those without IPV was 6.9%. PrEP interruption was significantly associated with IPV after adjustment for age and frequency of sexual intercourse (adjusted odds ratio = 2.6, 95% confidence interval: 1.2 to 6.0). Conclusions: IPV was more likely to be reported at visits when PrEP interruptions were also reported, which may have implications for sustained adherence to PrEP. Within PrEP delivery programs, there may be opportunities to assess individual safety and well-being to bolster adherence.